2010
DOI: 10.5551/jat.4960
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the Vasodilatation Capability of the Brachial Artery in Patients with Idiopathic Venous Thrombosis

Abstract: Aim: Determination of the functional capability of the peripheral arteries is increasingly used as an early marker of vessel disease. The aim of this study was to evaluate flow-mediated (FMD) and glyceryl trinitrate-mediated (NMD) dilation of the brachial artery in patients with idiopathic venous thrombosis (VT). Methods: Flow-mediated brachial artery dilatation and the dilatation response to glyceryl trinitrate were measured using high-resolution ultrasound in 97 subjects (49 eligible patients of both sexes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…We showed that idiopathic VT is associated with impaired flow-mediated and glycerin trinitrate-mediated vasodilatory response of the brachial artery. 26 This suggests a relationship between VTE and atherosclerosis. We also showed that idiopathic VT is associated with long-term increased levels of markers of endothelial damage (vWF and P-selectin).…”
Section: 24mentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that idiopathic VT is associated with impaired flow-mediated and glycerin trinitrate-mediated vasodilatory response of the brachial artery. 26 This suggests a relationship between VTE and atherosclerosis. We also showed that idiopathic VT is associated with long-term increased levels of markers of endothelial damage (vWF and P-selectin).…”
Section: 24mentioning
confidence: 99%
“…Results from the MAinISar-THROmbosis registry suggested that arterial hypertension was an independent risk factor for recurrent VTE. 30 As in both diseases endothelial function deteriorates, 26,31 ED could be the link between these 2 diseases. This is in agreement with the reports of efficacy of some antihypertensive drugs on risk of VTE.…”
Section: 24mentioning
confidence: 99%
“…All techniques for direct determination of venous endothelial function are complicated and their reproducibility is limited; therefore, measurement of endothelial function of the peripheral arteries is frequently used as a surrogate to assess venous endothelial function 52,53) . Namely, in subjects with deteriorated arterial endothelial function, venous endothelial dysfunction is also expected.…”
Section: Peripheral Arterial Tonometrymentioning
confidence: 99%
“…11, 12 The vascular endothelium regulates the functional capabilities of the entire circulatory system; in patients with endothelial dysfunction of the peripheral arteries, the venous functional status may have deteriorated as well. [13][14][15] Reactive hyperemia-peripheral arterial tonometry (RH-PAT) is a noninvasive, automatic, and less operator-dependent clinical test that is used to evaluate peripheral endothelial function. 16 In a community-based cohort, Hamburg et al 17 reported a significant relationship between RH-PAT and cardiovascular risk factors.…”
Section: Qthrombosis Scorementioning
confidence: 99%